Narasi Moderasi Beragama dalam Manuskrip Melayu Kawasan Borneo: Sebuah Model Penerapan Pendidikan Inklusi - Iskandar Iskandar; Materan Materan (LP. Ma'arif Janggan Magetan, 2024)
Manuscript-based religious moderation narratives remain rarely studied, although manuscripts contain valuable thoughts and experiences that can serve as models for developing religious moderation in the homeland, especially in modern education. There are three Borneo Malay manuscripts worthy of exploration in terms of their narratives: the Panji Salatin manuscript (1605-1635), the Hikayat Banjar Manuscript (1859), and the Pangeran Syarif Manuscript (1870). This research aims to explore the narrative forms and moderation values contained within them. Based on philological and historical approaches, it can be concluded that: a. The Borneo Malay manuscripts contain various narratives, namely: juridical narrative, historical narrative, and prose literary narrative. b. The Borneo Malay manuscripts contain principles and symbols of religious moderation, including: principles of equality and justice, principles of preservation and respect for local culture, principles of non-violence, cultural symbols, and language; c. The principles and symbols of religious moderation contained in the Borneo Malay Manuscripts provide important implications for the development of inclusive education today.